PENGARUH EVA, RI, EARNINGS, DAN AKO TERHADAP RETURN SAHAM - Hendra Imam Saputra, 06.05.52.0100; Indarti, MG. Kentris (Students Journal of Accounting and Banking, 2012)
The success of a company in maintaining its existence did not escape the influence of the role of financial managers and financial decisions that have been made. If the company has a goal to double the shareholder value, the measure used to assess the performance of the company, should have a direct connection with the return received by shareholders.Formulation of the problem of this study was to determine the influence of EVA, RI, Earnings and Operating Cash Flow Return on stock. The population in this study is a manufacturing company listed on the Stock Exchange in the year 2006 to 2008. The number of samples obtained are as many as 67 companies during the 3 years of observation, using purposive sampling technique. The analysis of the test data used is multiple linear regresion.Based on these results it can be concluded that the EVA, RI, and Operating Cash Flow does not have a significant effect on stock return. Earnings while having a positive impact on Stock Return.Keywords: EVA, RI, Earnings, Operating Cash Flow, and Return on Stock.